Frequency and Antimicrobial Resistance Patterns of Salmonella Enterica Isolates in a Tertiary Care Setting - Asma Ejaz, Aneela Khawaja, Kiran Fatima, Nusrat Alavi, Maliha Asif, Abeer (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Typhoid fever is endemic in South Asia and is the most common bacteremic illness in children in Pakistan, with rates as high as 1000 cases per 100000 child-years having been reported from Karachi. The occurrence of multidrug-resistant (MDR) Salmonella enterica strains has been highly reported from developing countries. Fluoroquinolone resistance has also been highly reported. Clinical cases of cephalosporin-resistant Salmonella enteric isolates have also been reported recently leading to spread of XDR strains. Methodology; Between 1st January-31st December 2021, a total of 1385 blood sample were processed for identification of enteric fever isolates. The blood samples were inoculated in the tryptic soy broth bottles. The strain identification was initially performed by Gram staining, and by using API 20E. For serovar confirmation, agglutination assays were performed using antisera. The antimicrobial susceptibility testing for the Salmonella enterica isolates was performed using the disc diffusion method according to the (CLSI) standards for the following antibiotics; ampicillin, amoxicillin, piperacillin-tazobactam, ceftriaxone, cefotaxime, cefepime, imipenem, meropenem, ciprofloxacin, chloramphenicol and trimethoprim-sulfamethoxazole Results: A total of 425(30.68%) samples gave positive growth. Sixty-two (14.58%) isolates were identified as Salmonella enterica species. Eight isolates (12.90%) were from < 5 years of age group, 35(56.45%) from 5 to 15 years age group. Species differentiation revealed, 52(83.87%) were Salmonella typhi and 10(16.12%) were Salmonella paratyphi A. Sensitivity pattern of the isolates (n=62), indicated 29(46.77%) were multi-drug resistant (MDR), while 32(51.61%) were extensively-drug resistant (XDR). Conclusions: Both governmental and nongovernmental organizations in Pakistan need to actively promote vaccination campaigns and healthy hygiene habits and discourage irrational use of antibiotics to prevent the mortality and morbidity associated with increasing antibiotic resistance in pathogens. Safe water supply, personal hygiene and effective antibiotic policies can help us to control the disease therefore reducing antimicrobial resistance.